Clinical Presentation of Acute Pulmonary Embolism in Patients with Coronavirus Disease 2019 (COVID-19) - Nonso Osakwe; Douglas Hart (Case Reports in Hematology)
The clinical management of severely ill patients with COVID-19-related acute respiratory distress syndrome (ARDS) presents significant challenges. Many COVID-19 patients with ARDS also present with laboratory findings significant for derangement in coagulation function. In this report, we describe acute pulmonary embolism in three patients with COVID-19. We assessed the role of D-dimer assay and anticoagulation treatment in these patients. The aim of this case report is to increase awareness about the use of D-dimer in addition to patient’s clinical status for making treatment decision in COVID-19 patients.